Alogenní transplantace krvetvorných buněk u nemocných s chronickou myeloidní leukemií v České republice: retrospektivní hodnocení výsledků z let 1988 až 2005 - Faber, Edgar; Koza, Vladimír; Vítek, Antonín; Mayer, Jiří; Sedláček, Petr; Žák, Pavel; Zapletalová, Jana; Benešová, Kateřina; Krejčová, Hana; Steinerová, Kateřina; Marešová, Ivana; Cetkovský, Petr (Vnitřní lékařství, 2006)
Analyses of hematopoietic stem cell transplantation (SCT) results are of high importance for decision-making on treatment strategy for patients with SCT as a possible therapeutic alternative. In this paper the Czech National Registry of SCT and Transplantation Centre in Pilsen present their joint retrospective analysis of the results of allogeneic SCT in patients with chronic myeloid leukemia (CML) performed in the Czech Republic from 1988 to spring 2005. 295 patients (179 men and 116 women) ranging in age from 6.9 to 59.5 years (median 37.3) underwent transplants. In most cases the donor was an HLA-identical sibling (164; 55.6%) or a voluntary unrelated donor from the register (110; 37.3%), in a minority of cases another relative of the patient (21; 7.1%). Myeloablative conditioning was used in 90% of patients. The source of hematopoietic stem cells was bone marrow in 57%, peripheral blood in 41% and combination of both in 2% of cases. 83.4% of patients underwent transplant in the chronic phase of the illness while 7.8% in the acceleration phase and 6.1% in the blastic phase respectively. The median interval from the diagnosis to SCT was 316 days. Median follow-up after SCT was 2 years. SCT was complicated by acute graft versus host disease of grade II-IV in 33.7% of patients and by chronic graft versus host disease in 36.3% of patients. Median survival was not reached, 18 (6.1%) of patients died due to the relapse of CML and the cause of 101 (34.2%) deaths was transplant-related. Significant trends were observed during the study period: SCT were performed more frequently in older patients, less than one year from the diagnosis, reduced-intensity conditioning was used more often and the source of hematopoietic stem cells was peripheral blood in the majority of patients (p = 0.188 - < 0.0001). Also, transplantation activity changed - the annual rate of SCT increased steadily until 1999, while there was no such an increase between 2000 and 2005. The use of peripheral stem cells was associated with chronic graft versus host disease (p = 0.007). In Cox multivariate analysis the EBMT risk score and the interval from the diagnosis to SCT were identified as independent factors in patient survival. An "ideal" patient, aged under 30, undergoing transplant in the chronic phase of CML within one year since the diagnosis after 2000 had a survival probability of 88% for three years after SCT. It can be concluded that results of allogeneic SCT in CML in the Czech Republic reflect current global trends, are comparable with results achieved in other countries and show significant improvements.
Keywords: finanční podpora výzkumu jako téma; reakce štěpu proti hostiteli; dárci tkání; hodnocení rizik; Graft vs Host Reaction; Tissue Donors; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; Survival Analysis; transplantace hematopoetických kmenových buněk; chronická myeloidní leukemie; příprava pacienta k transplantaci; Transplantation Conditioning; Risk Assessment; transplantace kostní dřeně; retrospektivní studie; Research Support as Topic; Transplantation, Homologous; analýza přežití; Bone Marrow Transplantation; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Retrospective Studies; Humans